Eds. Lobanov, N. A., Mažeikienė, N., Skvortsov, V. N. 2013. Continuous education as a prerequisite of the development of professional competences - Kula, Ewa; Maliszewski, Tomasz (Respectus Philologicus, 2014)
Continuous education as a prerequisite of the development of professional competences. Monography. Eds. N. A. LOBANOV, N. MAŽEIKIENĖ, V. N. SKVORTSOV. Saint-Petersburg: Pushkin Leningrad State University, 2013. 280 pp. ISBN 978-5-8290-1275-5.